Meningkatkan Prestasi Belajar Peserta Didik melalui Manajemen Sarana dan Prasarana di Sekolah - Herianto, Rudi; Sanuhung, Fitriyani; Wajdi, Muhammad Farid (Lembaga Yasin AlSys, 2021)
This research was conducted to determine the effect of facilities and infrastructure in improving student achievement and how the invisible relationship between the management of facilities and infrastructure with student achievement. Facilities and infrastructure are one of the supporting factors so that students' academic and non-academic achievements in schools can increase, through good management of facilities and infrastructure that can meet the needs of students, teachers, staff, and school employees. Student achievement can increase if the management of facilities and infrastructure can be carried out effectively and efficiently. Facilities and infrastructure are not only carried out by maintaining them but facilities must be managed through planning, procurement, management, maintenance.